Role of artificial intelligence in enhancing mechanical ventilation – A peek into the future - Neeraj Pal Singh; Masood Ali Mujawar; Akash Golani (Indian Journal of Anaesthesia, 2025)
This article explores recent advancements in the role of artificial intelligence (AI) in enhancing mechanical ventilation (MV), accentuating its potential to mitigate risks such as ventilator-induced lung injury, ventilator-associated pneumonia and asynchronies. The integration of AI, including machine learning, natural language processing and predictive analytics, into MV is reshaping the landscape of critical care, offering advanced solutions to enhance patient outcomes with real-time monitoring, personalised ventilation strategies, early detection of complications and also increased operational efficiency. Key practical issues surrounding the implementation of AI into existing clinical workflows, including data quality, data sharing and privacy, data standardisation, seamless integration with existing healthcare systems, transparency of algorithms, interoperability across multiple platforms, patient safety and addressing ethical concerns, remain. As we advance, a collaborative approach between AI and healthcare professionals will be essential to ensure optimal patient safety.